The effect of drill and play methods on karate students' Gyaku Tsuki Kumite skills - Tahan Aritonang; Damrah Damrah; Syahrial Bakhtiar; Ardo Okilanda (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aimed to examine the effect of Drill and Game-Based Practice on Kumite Gyaku Tsuki technique skills among extracurricular Karate students at SMK Negeri 1 Bintan Utara. A total of 31 male students from grade 10 participated and were divided into an experimental group (n = 16) receiving Drill and Game-Based Practice, and a control group (n = 15) following conventional Karate training. The study employed a quasi-experimental design with pretest and posttest assessments. Skill performance was measured through standardized Kumite Gyaku Tsuki tests evaluated by certified national Karate referees. Data were analyzed using descriptive statistics, paired t-tests, and independent sample t-tests. Results indicated significant improvements in both groups, with the experimental group showing a greater increase in posttest scores (Mean = 42.13) compared to the control group (Mean = 33.47). Statistical analysis confirmed a significant difference between groups (p < 0.05). In conclusion, Drill and Game-Based Practice effectively enhances Kumite Gyaku Tsuki skills, and incorporating game-based exercises offers superior results compared to conventional training methods.